2016
DOI: 10.1007/s10734-016-0012-1
|View full text |Cite
|
Sign up to set email alerts
|

The work–study interface: similarities and differences between ethnic minority and ethnic majority students

Abstract: Given the poorer academic outcomes of non-Western ethnic minority students compared to ethnic majority students, we investigated whether differences exist in workstudy interface between ethnic groups. We tested a work-study interface model, in which the work-related factors work-study congruence, job control, job demands, work hours, job involvement and job support were antecedents to work-study facilitation (WSF) and workstudy conflict (WSC). WSC and WSF, in turn, were expected to predict students' study effo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
(90 reference statements)
2
5
0
Order By: Relevance
“…The existence of employees who continue S2 and still have the status of employees, of course, raises a double burden as a result of the dual roles carried out. This is in accordance with research conducted by Setyowati and Nurhayati (2019), Meeuwisse et al, (2017), Owen et al, (2017), Sadiq (2020) and Putra (2017) which found that workload has an influence on the perceived of organizational support for work school conflict.…”
Section: E Relationship Of Workload On Work School Conflictsupporting
confidence: 92%
“…The existence of employees who continue S2 and still have the status of employees, of course, raises a double burden as a result of the dual roles carried out. This is in accordance with research conducted by Setyowati and Nurhayati (2019), Meeuwisse et al, (2017), Owen et al, (2017), Sadiq (2020) and Putra (2017) which found that workload has an influence on the perceived of organizational support for work school conflict.…”
Section: E Relationship Of Workload On Work School Conflictsupporting
confidence: 92%
“…These students must adapt and/or develop resources to meet the demands. Furthermore, given that students are likely to continue these extracurricular activities while studying [ 42 ], it might even cause a conflict for them between life domains, resulting in enhanced stress perception [ 43 ] and lower academic performance [ 44 , 45 ]. Thus, the difference in stress perception levels between students selected by high grades and assessment might be explained by a better alignment between the resources of the students and the demands of medical school for students selected by high grades compared to students selected by assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Thereby, it might even worsen the shortage of qualified teachers in the long run. The frequency of student employment within teacher education is unknown, but students in general increasingly opt to combine their study with employment (Beerkens et al, 2011;Meeuwisse et al, 2017;Quintini, 2015). Beerkens et al (2011) report that approximately half of all students work alongside their studies in Europe (47%), the United States (49%) and Australia (50%).…”
Section: Introductionmentioning
confidence: 99%